DIFFERENTIATION OF SPINAL TUBERCULOSIS AND METASTATIC SPINAL TUMOR USING MRI FEATURE: A SYSTEMATIC REVIEW - Justicia Izza Tsuroya; Muhammad Faris; Paulus Rahardjo (Majalah Biomorfologi, 2023)
Highlights1. Lesions that are regularly diagnosed in the spine include TB of the spine and tumors that have spread throughout the body.2. The examined papers included 35 individuals with tuberculous spondylitis and 31 patients with metastatic spinal malignancies.3. A methodology for MRI imaging and an accurate medical history will aid in establishing an accurate diagnosis. AbstractBackground: Spinal tuberculosis and metastatic tumors are commonly diagnosed lesions in the spine. Tuberculosis spondylitis, also known as Pott's Disease, is the most common extrapulmonary tuberculosis disease. MRI is the gold standard for early diagnosis because there is no significant difference in the results of clinical manifestations and histopathological examination. A biopsy will usually be used for a final exam for diagnosis. Objective: To provide information to confirm the diagnosis of TB spondylitis cases and metastatic spinal tumors. Method: A literature search was conducted via PubMed, Science Direct, and Scopus by selecting studies according to inclusion and exclusion criteria. The quality and risk of bias assessments were performed using Joanna Briggs Institute (JBI) tools. Overall, 35 spinal tuberculosis and 31 metastatic spinal tumor patients from 2 studies were reviewed. Result: Of the 35 patients with tuberculous spondylitis and 31 patients with metastatic spinal tumors from the two studies reviewed. It was found that the thorax was the most common region. The following imaging findings were of statistical significance (p<0.05): skip lesion, solitary lesion, intraspinal lesion, concentric collapse, abscess formation (paraspinal, intraosseous, and epidural lesions), and syrinx formation. Conclusion: An MRI imaging protocol and correct medical history will help establish an accurate diagnosis. Skip lesions, abscesses, and modular lesion margins are considered for diagnosis.